Anatomy, physiology, and pathophysiology of the pedunculopontine nucleus. - Jenkinson, N; Nandi, D; Muthusamy, K; Ray, N; Gregory, R; Stein, J; Aziz, T (2009)
The pedunculopontine nucleus is composed of cholinergic and non-cholinergic neurones and is located in the caudal pontomesencephalic tegmentum. Evidence suggests that the nucleus plays a role in the production and control of movement. The nucleus has dense interconnections with the basal ganglia, as well as with other areas of the brain associated with motor control. Electrical stimulation of the pedunculopontine nucleus in the decerebrate cat or rat produces organized locomotor movements. Physiological studies show that the pedunculopontine nucleus modulates its activity in response to locomotion, as well as voluntary arm and eye movements. Degeneration of the pedunculopontine nucleus is seen in post-mortem brains in humans with Parkinson's disease and Parkinsonian syndromes. In animal models of Parkinson's disease, metabolic changes are seen in the pedunculopontine nucleus, and chemical inhibition or mechanical disruption of the nucleus can produce an akinetic state in animals and man. In this paper we review the literature in support of the suggestion that some of the symptoms of Parkinson's disease are caused by dysfunction of the pedunculopontine nucleus. In accordance with this view, direct stimulation of the nucleus can ameliorate some symptoms of the disease, as demonstrated in both experimental animals and man.